PERENCANAAN, PENGEMBANGAN DAN PELAKSANAAN EVALUASI PEMBELAJARAN PAI DI SDN 064988 MEDAN JOHOR - Hayat Harahap, Mardianto, Wahyuddin Nur Nasution (Pascasarjana UIN Sumatera Utara, 2018)
ABSTRACT: This research is aimed to know 3 things, that is: (1) to know the planning of learningof PAI at SDN 064988 District of Johor, 2) to know the development of learning of PAI at SDN064988 District of Johor, and (3) to know the implementation of learning evaluation of PAI at SDN064988 Kecamatan Medan Johor. This research is a qualitative descriptive study. The results ofthis study are: (1) PAI teachers also have done planning PAI learning well. The role of headmasteris very helpful for PAI teachers in PAI learning planning. Supporting Fator in PAI lesson planning atSDN 064988 Medan Johor is with the availability of adequate facilities so that PAI subject teachersdo not feel any obstacles at all. (2) the efforts of PAI teachers in conducting PAI learning developmentis to establish supervision of each work unit conducted by Islamic Religious teachers includingthe process of teaching and learning activities. Supporting factors in the development oflearning PAI at SDN 064988 Medan Johor is with the availability of facilities that are very adequateso that the subjects of PAI teachers do not feel any barriers at all. (3) teachers of PAI SDN064988 Medan Johor have conducted PAI learning evaluation well. Supporting Fator in the implementationof PAI learning evaluation at SDN 064988 Medan Johor is with the availability of adequatefacilities so that PAI subjects teachers do not feel any barriers at all.ABSTRAK: Penilitian ini bertujuan untuk mengetahui 3 hal, yaitu: (1) untuk mengetahui perencanaanpembelajaran PAI pada SDN 064988 Kecamatan Medan Johor, (2) untuk mengetahui pengembanganpembelajaran PAI pada SDN 064988 Kecamatan Medan Johor, dan (3) untuk mengetahui pelaksanaanevaluasi pembelajaran PAI pada SDN 064988 Kecamatan Medan Johor. Penelitian ini merupakanpenelitian deskriptif kualitatif. Hasil penelitian ini adalah: (1) guru PAI juga telah melakukanperencanaan pembelajaran PAI dengan baik. Peran kepala sekolah sangat membantu guru PAIdalam perencanaan pembelajaran PAI. Fator Pendukung dalam perencanaan pembelajaran PAI diSDN 064988 Medan Johor adalah dengan tersedianya sarana yang sangat memadai sehinggaguru mata pelajaran PAI tidak merasa mengalami hambatan sama sekali. (2) upaya guru PAIdalam melakukan pengembangan pembelajaran PAI ialah dengan membentuk supervisi setiapsatuan kerja yang dilakukan oleh guru Agama Islam termasuk proses kegiatan belajar mengajarnya.Faktor Pendukung dalam pengembangan pembelajaran PAI di SDN 064988 Medan Johor adalahdengan tersedianya sarana yang sangat memadai sehingga guru mata pelajaran PAI tidak merasamengalami hambatan sama sekali. (3) guru PAI SDN 064988 Medan Johor telah melaksanakan